The Integration of Global Competence Into Malaysian English as a Second Language Lessons for Quality Education (Fourth United Nations Sustainable Development Goal) - Yaccob, Nur Syafiqah; Yunus, Melor Md; Hashim, Harwati (Frontiers in Psychology, 2022)
Research in the globalization era has emphasized the importance of global competence and its integration into language teaching and learning. This article discussed the current focus of global education through the integration of global competence in English as a Second Language (ESL) in Malaysia. The country’s global competence development among ESL teachers and students, along with its integration into English lessons, were identified, satisfying the need to achieve quality education. The global competence integration of ESL teachers will meet the fourth United Nations Sustainable Development Goal (SDG 4), which strives for quality education. The global education goals form a critical starting point of this article, which articulates the connection to the targets in SDG 4. Hence, this article investigated the significance of global competence in language teaching and learning in Malaysia. Overall, the integration of global competence among ESL teachers can provide life-long learning, enhancing the quality of education.